Teaching Trigonometry Using Khan Academy Application - Cartagena, Mary Joy; Inoferio, Hermie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of the Khan Academy application as a primary instructional material in teaching Trigonometry, specifically the Law of Sines, Law of Cosines, and Oblique Triangles, among Grade 9 students at Aloran Trade High School during the School Year 2025–2026. Anchored on Bloom’s Mastery Learning Model and supported by the concepts of immediate feedback and the Input-Process-Output (IPO) Model, the study utilized a quasi-experimental non-randomized control group pre-test–post-test research design. Two intact Grade 9 classes participated in the study, consisting of a Control Group taught through conventional lecture-discussion methods and an Experimental Group that utilized the Khan Academy application integrated with face-to-face instruction and mastery-based activities. A validated 30-item standardized assessment instrument with a KR-20 reliability coefficient of 0.817 was administered as both pre-test and post-test. Data were analyzed using Mean Percentage Score (MPS), paired samples t-test, independent samples t-test, and Cohen’s d effect size. The findings revealed that both groups initially demonstrated Beginning-level proficiency in Trigonometry and showed significant improvement after instruction. However, the Experimental Group achieved significantly higher post-test performance and greater mean gain scores compared to the Control Group, indicating that the Khan Academy application enhanced students’ mastery and proficiency more effectively than conventional instruction alone. Students identified instant feedback, mastery-based activities, and interactive visualization as beneficial features, although technical challenges such as unstable internet connectivity and limited mobile device functionality affected usability. The study concluded that blended learning integrating digital mastery tools and teacher support is an effective approach for improving mathematical understanding and academic performance. The study supports Sustainable Development Goal (SDG) 4 on Quality Education through the promotion of accessible and technology-enhanced learning. It also aligns with SDG 9 on Industry, Innovation and Infrastructure by encouraging the integration of digital platforms into classroom instruction. The findings contribute to educational sustainability by supporting technology-driven, learner-centered instruction and strengthening institutional practices for data-driven and adaptive learning environments.
Keywords: Blended Learning; Khan Academy Application; Mastery Learning; Mathematics Performance; Oblique Triangles; Trigonometry; Technology-Enhanced Learning; Traditional Instruction